Braidotti, Spinoza and disability studies after the human. (December 2017) - Abrams, Thomas
Disability studies has begun to employ Rosi Braidotti's posthumanism, as a means to challenge the exclusionary model of man, dominant both in the academy and in everyday life. Braidotti argues that we must embrace a new form of subjectivity to effectively address the academic, environmental and species challenges characterizing the posthuman condition. This critical posthuman subject is inspired, in part, by Baruch de Spinoza, read as a monistic philosopher of difference. In this article, I compare Braidotti's posthuman philosophy with Spinoza's Ethics, read through a Deleuzian lens. The two projects are extremely different. My arguments are twofold: first, that Braidotti's subjective reading overlooks Spinoza's anti-subjective rationalism; and, second, that we must be cautious about Braidotti's demands that we jettison all vestiges of man from philosophy, exploring disability or anything else. I make my case using the example of phenomenology. I end by asking what an expanded understanding of Spinoza's philosophy means for disability studies, for posthumanism and for other forms of radical philosophy in the future.